Business networks and inward FDI policy - Fergal McCann (University College Dublin, UCD School of Economics, 2008)
I outline the effect of business networks on trade, FDI and welfare in a two-country, two-firm duopoly. The network effect, following Greaney (2002), is modelled as a marginal cost disadvantage facing a firm from Foreign in selling to Home. Unlike traditional trade costs, this cost cannot be avoided by investing in Home. My main addition is a Nash game between governments in which they subsidise the fixed costs of inward FDI. While the network effect is shown to lead to favourable outcomes for the Home firm, I show that once government subsidies to the fixed costs of FDI are included and welfare functions analysed, the network effect leads to asymmetric outcomes unfavourable to Home. This result can help inform the debate on countries' (in particular Japan's) international trade and investment relations.
Keywords: F12; F23; L52; 330; Foreign Direct Investment; Network Effects; Government Subsidies